Staying in the loop : international alliances for sharing technology - Mody, Ashoka (World Bank Discussions Papers, 1989)
Firms in the organization for economic cooperation and development (OECD) countries have formed a large number of alliances to share technology. These alliances include various contractual arrangements: formal research consortia, informal ties, and production and marketing joint ventures. The motivation and form of the alliance tend to change as the product cycle and market structure evolve.